3D Printing Scaffold Vaccine for Antitumor Immunity. Issue 48 (15th October 2021) - Zhang, Yue; Xu, Jialu; Fei, Ziying; Dai, Huaxing; Fan, Qin; Yang, Qianyu; Chen, Yitong; Wang, Beilei; Wang, Chao
Abstract: Cancer vaccine platform has attracted great interest in the field of cancer immunotherapy. Here, 3D printed scaffolds loaded with immunoregulators are developed for enhanced cancer immunotherapy. The rapid manufacturing and precise molding based on 3D printing can realize the mass manufacturing of cancer vaccines and personalized design. Meanwhile, compared to the traditional hydrogel, the 3D‐scaffold with porous structure endows its similar functions compared with real lymphoid organs by recruitment of a great number of immune cells, leading to the formation of "artificial tertiary lymphoid structures, " where there is a promising site to enhance both humoral and cellular immune responses. Efficient anticancer immunity is induced when combined with immune checkpoint blockade to inhibit the tumor growth. Personalized antitumor scaffold vaccines are further demonstrated for filling of tumor site after surgery to prevent cancer metastasis. Taken together, these results promise the 3D printing scaffold vaccine as the potential strategy for cancer vaccine therapy in the future. Abstract : 3D printed scaffolds loaded with immunoregulators are developed for enhanced cancer immunotherapy. The implantable 3D scaffold vaccine with porous structure endows similar functions compared with lymphoid organs by recruiting immune cells and promoting antigen presentation, as well as inducing robust antitumor immune responses. This 3D scaffold vaccine is also capable of customized manufacturing and personalized treatment.